Towards appropriate institutional linkage structures for effective participatory and coordinated agricultural extension in Malawi - Duvel, G.H. (Gustav Heinrich) (University of Pretoria, 2013)
Dissertation (MSc Agric (Agricultural Extension))--University of Pretoria, 2007.